Study on Place Attachment of Street Vendors to the Trading Space in Alun-alun Jepara - Aisyah Farah Dina Purba; Dyah Titisari Widyastuti (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2022)
The old alun-alun of Jepara is the center of city activity and also used to be the center of street vendors activity. Since 2019, the local government decided to move all the street vendors activity into new alun-alun where is one kilometres away from the previous location. The majority of street vendor stated that the new location is not as comfortable as the previous location. It becomes their reason for illegally returning to trade in the old alun-alun. This research aims to examine how far is the place attachment influence for trading based on the preference of street vendors. The exploration of place attachment was based on three variables, i.e. attachment of person, process, and place. Qualitative research method was conducted through literature review, interview, and field observation. The result shows there is no influence of person and process in street vendors place attachment in trading. Only the physical and social form of place indicates the significant influence in place attachment. The factors of access, space shape and size, amenities, and attractiveness activity contribute to the place attachment in trading that is not found yet in new alun-alun.